Porsi Konsumsi Sayur dan Buah Signifikan Menurunkan Asupan Energi: Sistematik Review - Nursalim .; Chaerunnimah .; Abdullah Thamrin; Dien Abdul Munir; Sirajuddin . (Media Gizi Pangan, 2020)
AbstractBackground of this study is that controlling body weight is one of them by increasing the consumption of vegetables and fruit, because it has a lower energy content than other food ingredients such as energy sources (staple foods and side dishes).Objective of this study was to determine the amount of vegetable and fruit intake that can reduce energy intake.Method is a systematic review by tracing various studies related to vegetable and fruit consumption on various search engines, namely PubMed, Scinapse, Nature. The search term used is "intake energy, vegetable and fruit" for English references. All references published between 2015-2020 were selected using the Prefered Preferred Reporting Items for Systematic Reviews and Meta-analyses (Prisma) method. The final result found that 6 articles were read and a summary table of the research results was made.Results found that there were 6 articles discussing the theme of energy intake, vegetables and fruit. The amount of fruit and vegetable consumption is between 100-300 g per day, which can have a real effect on reducing energy intake.Conclusion is that decreasing energy intake is by increasing the intake of vegetables and fruits. Keywords: Energy intake, vegetables and fruit